2018
DOI: 10.1002/ijc.32043
|View full text |Cite
|
Sign up to set email alerts
|

New pharmacological effect of fulvestrant to prevent oxaliplatin‐induced neurodegeneration and mechanical allodynia in rats

Abstract: Oxaliplatin, which is widely used as chemotherapy for certain solid cancers, frequently causes peripheral neuropathy. Commonly described neuropathic symptoms include aberrant sensations such as mechanical allodynia (hypersensitivity to normally innocuous stimuli). Although oxaliplatin neuropathy is a dose‐limiting toxicity, there are no established preventive strategies available at present. By screening several sets of small‐molecule chemical libraries (more than 3,000 compounds in total) using a newly establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Fulvestrant, for the treatment of breast cancer, was screened from several small-molecule chemical libraries including more than 3,000 compounds and reduced oxaliplatin-induced neuronal damage in a cellular model ( Yamamoto et al, 2019 ). Consistent with these in vitro effects, fulvestrant also exerted neuroprotective effects in an oxaliplatin-CIPN rodent model, by preventing sciatic nerve axonal degeneration and the development of mechanical allodynia ( Yamamoto et al, 2019 ). However, the mechanism of this neuroprotective effect remains unclear.…”
Section: Drug Repositioning Study For the Prevention And Treatment Ofmentioning
confidence: 99%
“…Fulvestrant, for the treatment of breast cancer, was screened from several small-molecule chemical libraries including more than 3,000 compounds and reduced oxaliplatin-induced neuronal damage in a cellular model ( Yamamoto et al, 2019 ). Consistent with these in vitro effects, fulvestrant also exerted neuroprotective effects in an oxaliplatin-CIPN rodent model, by preventing sciatic nerve axonal degeneration and the development of mechanical allodynia ( Yamamoto et al, 2019 ). However, the mechanism of this neuroprotective effect remains unclear.…”
Section: Drug Repositioning Study For the Prevention And Treatment Ofmentioning
confidence: 99%
“…For instance, neuroinflammation modulation achieved using anti-macrophage-derived high mobility group box 1 (HMGB1) neutralizing antibodies reduced the severity of OIPN in a mice model [57]. On a similar hypothesis stands the observation that the synthetic derivative of progesterone, 17α-hydroxyprogesterone caproate (HPGC) is able to prevent OHP-induced allodynia as well as glial activation in mice [58]. New methodological approaches might also be helpful to drive the preclinical investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, investigations might also originate from the experience gained in other neurological diseases. For instance, the multiple sclerosis oral treatment dimethyl fumarate acting via up-regulation of the nuclear factor-erythroid-2-related factor 2 (Nrf2)-dependent antioxidant response was tested in vitro, showing positive results against oxaliplatin-, cisplatin-, and bortezomib-(but not paclitaxel-) induced inhibition of neurite outgrowth [58]. A different hypothesis is at the basis of the use of the anti-Parkinson's disease benztropine, an anti-histamine and dopamine re-uptake inhibitor with neuroprotective effects in neurodegenerative neurological disease models as well as in experimental diabetic neuropathy, that reduced OIPN severity in OHP-treated mice synergizing its anti-tumoral effect [60].…”
Section: Discussionmentioning
confidence: 99%
“…For the antioxidant therapies, our previous findings revealed that Nrf2 may have acted as a critical role in the progression of OIPN, with its ability of mitochondrial function protection and the inhibition of expression of the TRP protein family. The therapeutic or pharmacological activation of Nrf2 may be used to prevent or ameliorate the progression of OIPN without affecting the cytotoxicity of OHP [ 67 , 80 , 201 ]. Novel mitochondria-targeting antioxidants SS-31 prevented acute neuropathy symptoms caused by OHP in mice [ 164 ].…”
Section: Chemotherapy-induced Peripheral Neuropathy Prevention and Treatment: Therapy Candidates For Oipnmentioning
confidence: 99%
“…The neuroprotective agent niclosamide displayed potential antitumor and neuroprotective effects without affecting the cytotoxicity efficacy of OHP [ 202 ]. The 17α- hydroxyprogesterone caproate (HPGC), a synthetic derivative of progesterone, prevented the allodynia induced by OHP and glial activation in mice [ 201 ]. The anti-Parkinson’s agent benztropine, an anti-dopamine and histamine reuptake inhibitor, reduced OIPN severity in the OHP mouse model, synergizing its anti-tumoral effect [ 118 ].…”
Section: Chemotherapy-induced Peripheral Neuropathy Prevention and Treatment: Therapy Candidates For Oipnmentioning
confidence: 99%